Cluster mechanism for hot data storage in HBase system - Mohammad Musa Al-Momani (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The evolution in different areas like e-business contributed to increase the number of data. So, a scalable database is required to accommodate a large number of data. Moreover, this data could be important and the number of accessing for reading or writing operations can make a pressure in some servers more than others, this pressure called unbalanced accessing. This will be achieved if a system that guarantees the distribution of this important data in useful form is used, because the pressure can causes a delay. Accordingly, when we design a multi storage node to keep this data, the pressure will transfer from a server to another. So, the proposed system searched for a satisfied solution to distribute all the users on the servers in a useful way to detect any mistake or repeating updating operation data by using identification feature. This method is applied on Hbase and called Clusterization.